2019
DOI: 10.14710/nmjn.v10i1.23244
|View full text |Cite
|
Sign up to set email alerts
|

Mental Distress in Rural Areas of Indonesia

Abstract: Background: There is a higher prevalence of mental distress in rural areas compared to urban areas in Indonesia. The rural areas of Indonesia have various socio-demographic and sophisticated cultural characteristics, but less exposed to foreign cultures. Thus, the study about the prevalence, associated factors, and predictors of mental distress in rural areas is necessary.Purpose: This study aimed to identify the population's status and related factors of mental distress in rural areas in Indonesia.Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Sources of chronic stressors included a loss of cohesion in social networks, the death of family members, maintaining financial security, and managing pain/chronic health conditions (Behera et al, 2016;Gong et al, 2012;Howorth et al, 2019;Saifullah et al, 2020;Scogin et al, 2016;Silverstein et al, 2020;Wang et al, 2001;Williams et al, 2016;Zhang, Nazroo, & Vanhoutte, 2021;Zhang, Wang, & Xu 2021;Zhang & Silverstein, 2022;Zhou et al, 2019;Zhou et al, 2021). Workers in agriculture, a large industry consisting of primarily older persons, encounter multi-dimensional and pervasive stressors daily (House of Commons, 2019;Jones-Bitton et al, 2020;Lin & Chen, 2018;Roy et al, 2017;Wang et al, 2001;Yazd et al, 2019).…”
Section: Chronic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources of chronic stressors included a loss of cohesion in social networks, the death of family members, maintaining financial security, and managing pain/chronic health conditions (Behera et al, 2016;Gong et al, 2012;Howorth et al, 2019;Saifullah et al, 2020;Scogin et al, 2016;Silverstein et al, 2020;Wang et al, 2001;Williams et al, 2016;Zhang, Nazroo, & Vanhoutte, 2021;Zhang, Wang, & Xu 2021;Zhang & Silverstein, 2022;Zhou et al, 2019;Zhou et al, 2021). Workers in agriculture, a large industry consisting of primarily older persons, encounter multi-dimensional and pervasive stressors daily (House of Commons, 2019;Jones-Bitton et al, 2020;Lin & Chen, 2018;Roy et al, 2017;Wang et al, 2001;Yazd et al, 2019).…”
Section: Chronic Stressmentioning
confidence: 99%
“…Yet, they also experience logistical barriers to social connections due to low broadband internet, transportation barriers, and diminished education opportunities (Abdul Manaf et al, 2016;Burnette et al, 2021;Carver et al, 2018;Hu et al, 2018;Liang et al, 2020;Lin & Chen, 2018;Slwinski et al, 2021;Zhang, Wang, & Xu , 2021;Zhou et al, 2021). These challenges to accessing social connection with community and religious organizations can lead to psychological distress and loneliness, and a risk of mental illness (Adjaye-Gbewonyo et al, 2019;Coleman et al, 2011;Fastame et al, 2022;Garabrant & Liu, 2021;Heron et al, 2021;Hu et al, 2018;Li et al, 2022;Luo et al, 2017;Ruan et al, 2022; Online Journal of Rural Nursing and Health Care, 23(1) https://doi.org/10.14574/ojrnhc.v23i1.725 105 Saifullah et al, 2020;Scott et al, 2013;Wang et al, 2001;Windley & Scheidt;1983;Yiengprugsawan et al, 2012;Zhou et al, 2021).…”
Section: Loss Of Social Belongingmentioning
confidence: 99%
“…This result is congruent with a study by Barazzetta and Ghislandi (2017), which concluded that family income influenced children's sleep problems, as well as by Bagley et al (2016) which showed that socioeconomic status was associated with more subjective complaints at night, more frequent waking at night, fatigue throughout the day and increased sleep disturbance and more pre-sleep worries. Occupation is also related to psychological distress in rural areas (Saifullah et al, 2020).…”
Section: Family Incomementioning
confidence: 99%